Tinjauan Kriminologis Terhadap Tindak Pidana Penganiayaan Yang Dilakukan Oleh Tahanan - Raodiah; Dewantara, Reka (Fakultas Hukum, Universitas Sawerigading Makassar, 2023)
Criminological Review of Criminal Acts of Abuse Committed by Detainees. The research methodology used is normative or doctrinal legal research which is basically an activity that will examine the internal aspects of positive law. Normative legal research is a type of legal research methodology that bases its analysis on applicable laws and regulations that are relevant to the legal issues that are the focus of the research. This research aims to determine the factors that cause criminal acts of abuse committed by detainees and efforts to overcome them. Based on the analysis of data and facts, the author concludes, among others: a) Factors that cause criminal acts of abuse committed by detainees. are inadequate detention room capacity, individual problems, lack of harmonious social relations between prisoners, b) To prevent abuse carried out by prisoners at the Class I State Detention Center in Makssar City, the security unit monitors each room and place where prisoners carry out activities during 1x24 hours. Apart from that, each block is guarded by general pickets. The general picket is tasked with guarding prisoners and ensuring that there is no disturbance of order in the detention center.